Operative Versus Nonoperative Management of Hemorrhage in the Postoperative Kidney Transplant Patient. Issue 6 (June 2020) - Buggs, Jacentha; Shaw, Robert; Montz, Frederic; Meruva, Venkat; Rogers, Ebonie; Kumar, Ambuj; Bowers, Victor
Background: Postoperative hemorrhage has been described at rates of 14% in kidney transplant (KT) literature. The preferred management of postoperative hemorrhage in this population is not well described. We hypothesized a difference in outcomes with operative versus nonoperative management of hemorrhage after kidney transplantation. Methods: We conducted a retrospective cohort study of consecutive KTs from 2012 to 2019 (living and deceased donors). We defined hemorrhage based on the objective finding of hematoma on either ultrasound or CT scan. Management was defined as operative (surgical intervention with or without transfusion) or nonoperative (with or without transfusion). Results: We performed 1758 KTs of which 135 (8%) demonstrated hematoma on ultrasound or CT scan (66 operative vs 69 nonoperative management). The clinical signs and symptoms of low urine output ( P = .044), drop in hemoglobin ( P < .001), abdominal pain ( P = .005), and MAP < 70 mm Hg ( P = .034) were 92.5% predictive of postoperative hemorrhage in our KT patients. There were no differences between groups based on medical history, preop anticoagulation, anastomosis type, cold ischemic time, lowest hemoglobin, delayed graft function, or complications. Patients with nonoperative treatment of postoperative hemorrhage had shorter lengths of stay ( P = .003), better graft survival ( P = .01), and better patient survival ( P = .01). Discussion: We found better outcomes of graft and patient survival with shorter lengths of stay when we utilized nonoperative management of postoperative hemorrhage in KT patients. Our findings suggest a role for conservative nonoperative management in select patients. Ultimately, it is the surgeon's choice on how best to manage postoperative hemorrhage.